Treponemapallidum Dysregulates Monocytes and Promotes the Expression of IL-1β and Migration in Monocytes Through the mTOR Signaling Pathway - Liu, Wen-Na; Jiang, Xiao-Yong; Xu, Yan-Zhu; Sun, Xiao-Han; Wu, Kai-Xuan; Hu, Xin-Lin; Lin, Yong; Lin, Li-Rong; Tong, Man-Li; Liu, Li-Li (Frontiers in Cellular and Infection Microbiology, 2020)
Monocytes are widely involved in the body’s defense response, and abnormally regulated monocyte subsets are closely related to the pathogenesis of various diseases. It is unclear whether Treponema pallidum (Tp) dysregulates monocyte subsets and impacts the functions of monocytes. This study aims to analyze the distribution of monocyte subsets in syphilis patients and the effect of Tp on monocyte functions to explore the pathogenesis of syphilis. Flow cytometry was employed to detect monocyte subsets. With or without pre-treatment with rapamycin, THP-1 cell migration stimulated by Tp was investigated by a Transwell migration assay, and THP-1 cell phagocytosis was studied using fluorescent microspheres. IL-1β and TNF-α expression was quantified by PCR and flow cytometry, while LC3 and mTOR were investigated in Tp-exposed THP-1 cells using western blotting. Tp infection led to an increase in the proportion of CD14++CD16+ monocytes and a decrease in the proportion of CD14++CD16- monocytes. In addition, Tp promoted monocyte (THP-1) CD14 and CD16 expression in vitro, induced the expression of IL-1β and TNF-α in a dose-dependent manner and promoted the migration and autophagy of monocytes. Furthermore, mTOR phosphorylation on monocytes was stimulated by Tp, and the levels peaked at 30 min. Pre-treatment with rapamycin (mTOR inhibitor) attenuated the expression of IL-1β and migration in Tp-exposed THP-1 cells. Tp abnormally regulates monocyte subsets and promotes migration, autophagy, and the expression of IL-1β and TNF-α in THP-1 cells. Meanwhile, the mTOR affected the expression of IL-1β and migration in Tp-exposed THP-1 cells. This study is important as it sheds light on the mechanism by which monocytes interact with Tp during infection.